Pengaruh Lingkungan Keluarga dan Lingkungan Sekolah Terhadap Kedisiplinan Siswa - Putri, Afrida Nesya; Mufidah, Nastiti (ASANKA : Journal of Social Science and Education, 2021)
This study aims to determine whether the family environment significantly influences the discipline of grade IX students at SMP Negeri 1 Magetan in the 2020/2021 academic year, to find out whether the school environment significantly influences the discipline of grade IX students at SMP Negeri 1 Magetan in the 2020/2021 academic year. and to find out whether the family environment and school environment significantly influence the discipline of class IX students at SMP Negeri 1 Magetan for the 2020/2021 school year. Using quantitative research methods with the type of ex-post facto research and data collection techniques, namely questionnaires and documentation. In this study a population of 339 students and a sample of 85 using a sampling technique, namely purposive sampling. From the results of the study it was found that the family environment had a significant effect on student discipline by 35.3% and the remaining 64.7% was influenced by other factors, the school environment had a significant effect on student discipline by 32.3% and the remaining 67.7% was influenced by by other factors and the family environment and school environment significantly influence student discipline by 47.4% and the remaining 52.6% is influenced by other factors.